Dynamics Analysis of Locomotive Transmission System based on Romax - Zhang Fulai; Zhang Yinghui; He Weidong; Shi Xiaochun (Jixie chuandong)
Taking a locomotive traction transmission system as research object,the relatively complete transmission system model is built considering shaft deformation,flexible body,motor and wheel rail friction factors. From the static,modal analysis and dynamics analysis of the model,finding the causes of noise and vibration are the transmission error and the partial load in gear meshing process,which lead to large meshing impact. Using the Monte Carlo method for tooth shape optimization to reduce the transmission error,the best plan is obtained,achieving the transmission error reduced by 73% and the partial load phenomenon has improved greatly.